Developing and Activated T Cell Survival Depends on Differential Signaling Pathways to Regulate Anti-Apoptotic Bcl-xL - Ruiqing Wang; Huimin Xie; Zhaofeng Huang; Weirong Shang; Zuoming Sun (Clinical and Developmental Immunology)
Survival of T cells in both the central and peripheral immune system determines its ultimate function in the regulation of immune responses. In the thymus, developing T cells undergo positive and negative selection to generate a T cell repertoire that responds to foreign, but not self, antigens. During T cell development, the T cell receptor α chain is rearranged. However, the first round of rearrangement may fail, which triggers another round of α chain rearrangement until either successful positive selection or cell death occurs. Thus, the lifespan of double positive (CD4+CD8+; DP) thymocytes determines how many rounds of α chain rearrangement can be carried out and influences the likelihood of completing positive selection. The anti-apoptotic protein Bcl-xL is the ultimate effector regulating the survival of CD4+CD8+ thymocytes subject to the selection process, and the deletion of Bcl-xL leads to premature apoptosis of thymocytes prior to the completion of the developmental process. In addition to its critical function in the thymus, Bcl-xL also regulates the survival of peripheral T cells. Upon engagement with antigens, T cells are activated and differentiated into effectors. Activated T cells upregulate Bcl-xL to enhance their own survival. Bcl-xL-mediated survival is required for the generation of effectors that carry out the actual immune responses. In the absence of Bcl-xL, mature T cells undergo apoptosis prior to the completion of the differentiation process to become effector cells. Therefore, Bcl-xL ensures the survival of both developing and peripheral T cells, which is essential for a functional immune system.